Studies on an efficient method for determining 3,3'-dimethylbenzidine in the workplace air - Joanna Kowalska; Anna Jeżewska (Nofer Institute of Occupational Medicine, 2016)
Background: 3,3'-Dimethylbenzidene (DMB) is a substance classified into the group of carcinogens. The value of maximum admissible concentration for this substance in the workplace air is not specified in Poland. Bearing in mind that DMB is used in domestic companies there is a need to develop a sensitive method for determining 3,3'-dimethylbenzidine in the work environment. Material and Methods: The method consists in passing DMB-containing air through sulfuric acid-treated glass fiber filters, washing out the substance settled on the filter, using water and solution of sodium hydroxide, liquid-liquid extraction with toluene, replacing dissolvent with acetonitrile and analyzing the obtained solution. Studies were performed using high-performance liquid chromatography (HPLC) technique. An Agilent Technologies chromatograph, series 1200, with a diode-array detector (DAD) and a fluorescence detector (FLD) was used in the experiment. In the test, an Ultra C18 column of dimensions: 250×4.6 mm, particle diameter (dp) = 5 μm (Restek) was applied. Results: The method is linear (r = 0.999) within the investigated working range of concentration 1.08-21.6 μg/ml, which is equivalent to air concentrations 2-40 μg/m3 for a 540 l air sample. The limit of detection (LOD) of quantification determination is 5.4 ng/ml and the limit of quantification (LOQ) - 16.19 ng/ml. Conclusions: The analytical method described in this paper allows for selective determination of 3,3'-dimethylbenzidine in the workplace air in the presence of 1,4-phenylenediamine, benzidine, aniline, 3,3'-dimethoxybenzidine, 2-nitrotoluene, 3,3'-dichlorobenzidine and azobenzene. The method is characterized by good precision and good accuracy, it also meets the criteria for procedures involving the measurement of chemical agents, listed in EN 482:2012. Med Pr 2016;67(1):43-50